Tidal downscaling from the open ocean to the coast: a new approach applied to the Bay of Biscay. (April 2018) - Toublanc, F.; Ayoub, N.K.; Lyard, F.; Marsaleix, P.; Allain, D.J.
Highlights: A new approach is proposed to tidal downscaling in 3D coastal models. The best tidal solution is not necessarily the best forcing for downscaling. The error on the M2 elevation in the Bay of Biscay is reduced by 75%. The success of the method is also assessed through its impact on circulation. Satellite altimetry is a powerful tool for tidal assessment. Abstract: Downscaling physical processes from a large scale to a regional scale 3D model is a recurrent issue in coastal processes studies. The choice of boundary conditions will often greatly influence the solution within the 3D circulation model. In some regions, tides play a key role in coastal dynamics and must be accurately represented. The Bay of Biscay is one of these regions, with highly energetic tides influencing coastal circulation and river plume dynamics. In this study, three strategies are tested to force with barotropic tides a 3D circulation model with a variable horizontal resolution. The tidal forcings, as well as the tidal elevations and currents resulting from the 3D simulations, are compared to tidal harmonics extracted from satellite altimetry and tidal gauges, and tidal currents harmonics obtained from ADCP data. The results show a strong improvement of the M2 solution within the 3D model with a "tailored" tidal forcing generated on the same grid and bathymetry as the 3D configuration, compared to a global tidal atlas forcing. Tidal harmonics obtained from satellite altimetry data are particularly valuable to assess the performance of each simulation. Comparisons between sea surface height time series, a sea surface salinity database, and daily averaged 2D currents also show a better agreement with this tailored forcing.